(untitled) (SIRJANĀ – A Journal Of Arts and Art Education, 2023)
I make an attempt to investigate the select eight paintings by Nepali artists through phenomenology. Nepali artists paint through their living experiences and convert forms into various metaphors in their artworks. Their creations connect with people of different professions in society and make them enter into a new consciousness. I further attempt to explore the relationship of Nepali art with the phenomena of the lives of Nepali artists. The select eight paintings by eight artists are explored here. The artworks are analyzed and interpreted in the qualitative method. In earlier times, Nepali paintings were not interpreted through phenomenological aspects. I argue that the form and colour they invented express their life experiences consciously. I conclude that the value of the living experiences of Nepali artists in the creative process helps in the development of Nepali contemporary art.